What about Darwin? : all species of opinion from scientists, sages, friends, and enemies who met, read, and discussed the naturalist who changed the world - Glick, Thomas F. (Johns Hopkins University Press, 2010)
"Charles Darwin and his revolutionary ideas inspired pundits the world over to put pen to paper. In this unique dictionary of quotations, Darwin scholar Thomas F. Glick looks over the shoulders of those who revered--or reviled--the great scientist. P.T. Barnum, Anton Chekhov, Mahatma Gandhi, Carl Jung, Martin Luther King Jr., Mao Tse-tung, Pius IX, Jules Verne, Virginia Woolf, and a host of others all had something to say." "What was it about Darwin that generated such widespread interest? His Origin of Species changed the world. Naturalists, clerics, politicians, novelists, poets, musicians, economists, and philosophers alike could not help but engage his theories. Whatever their view of his work, however, those who met Darwin in person were unfailingly charmed by his modesty, kindness, and honesty." "This diverse collection drawn from essays, letters, novels, short stories, plays, poetry, speeches, and parodies shows Darwin's ideas permeating all areas of thought. The quotations trace a broad conversation about Darwin across great distances of time and space, revealing his profound influence on the great thinkers of the nineteenth and twentieth centuries."--Jacket